Pengaruh Model Pembelajaran POE2WE terhadap Kemampuan Berpikir Kritis Siswa Kelas XI SMAN 8 Mataram - Syarifa Wahidah Al Idrus; Farhana Zaid Alamudi; Baiq Fara Dwirani Sofia (Lembaga Yasin AlSys, 2025)
Although students’ critical thinking skills have received wide attention in educational research, studies that specifically examine the implementation of the POE2WE learning model at the senior high school level remain relatively limited. This study aimed to analyze the effect of the POE2WE learning model on the critical thinking skills of Grade XI students at SMAN 8 Mataram in the 2025/2026 academic year. A quantitative approach with a quasi-experimental method was employed, using a pretest–posttest control group design involving 64 students selected through purposive sampling. Data were collected using an essay test consisting of five items that had been tested for validity and reliability, then analyzed through normality and homogeneity tests, followed by hypothesis testing using a t-test at a 0.05 significance level. The results showed a statistically significant difference in critical thinking skills between students taught using the POE2WE learning model and those receiving conventional instruction, with a significance value of 0.004 (< 0.05). These findings contribute to the development of constructivist learning theory and provide empirical support for the effectiveness of the POE2WE model in enhancing students’ critical thinking skills in the senior high school context. The study concludes that the POE2WE learning model plays an important role in developing critical thinking skills and deserves consideration as an alternative instructional approach in classroom practice.